PENGARUH MODAL USAHA DAN INOVASI PRODUK TERHADAP PENDAPATAN UMKM BAWANG GORENG DI KABUPATEN BREBES - Ullaya, Najla; Najla Afaf Ullaya; Ida Farida; Aryanto (Jurnal Riset Akuntansi, 2025)
Income is an important indicator of the sustainability and growth of MSMEs. In Brebes Regency, fried shallot MSMEs face the challenge of declining income due to limited business capital and a lack of product innovation. This study aims to analyze the effect of business capital and product innovation on the income of fried shallot MSMEs in Brebes Regency. The research method used is descriptive quantitative with multiple linear regression analysis. The population is this study consists of 204 MSMEs, with a sample of 67 respondents determined using the Slovin formula. The t-test result shows that business capital has a significant effect on income with a significance value of 0,005, while product innovation also has a significant effect with a significance value of < 0,001. The F-test results indicate that business capital and product innovation simultaneously have a significant effect on income with a significance value of < 0,001. The coefficient of determination shows that both variables explain 35,7% of the variation in income. While the remaining 64,3% is explained by other factors beyond this study.